Analisis Pengaruh CSR terhadap Manajemen Laba dengan Tata Kelola Perusahaan sebagai Variabel Moderasi - Meily Juliani; Cherry Ventty (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The purpose of this research is to examine the social responsibility of earnings management with corporate governance as a moderating variable. Earnings management is measured by using discretionary accrual to check how much earnings management the company has done. Corporate social responsibility uses the GRI G4 index, while corporate governance uses several governance characteristics, namely board size, independent directors, ownership concentration, and institutional ownership to measure their role in regulating the relationship between social responsibility and earnings management. The research sample used 32 non-financial companies listed on the Indonesian Stock Exchange from 2016 to 2020. The research results show that corporate social responsibility has no significant positive impact on earnings management. The board size, institutional ownership, and block holder ownership have no significant impact on the relationship between social responsibility and earnings management. Independent directors as a mediator have a significant positive impact on the relationship between social responsibility and earnings management.